Organizing The Ordinary City: How Labor Reform Strategies Travel to the US Heartland. (16th February 2017) - Doussard, Marc
Abstract: In New York, Chicago and Los Angeles, formal alliances between labor unions and community organizations have spurred successful workplace and policy organizing campaigns. As a result, the institutional form of the community–labor coalition is travelling to smaller, less unionized and more politically conservative cities, where the replication of established organizing strategies must contend with political, economic and institutional differences that often go unnoted. Comparing community–labor alliances in Indianapolis, St. Louis and Chicago, this article identifies heretofore unobserved conditions of possibility for successful urban labor organizing in the US. Compared to smaller cities, Chicago and the large urban areas from which ideal practices are abstracted feature higher levels of union membership, significantly more funding of basic social and neighborhood services, and larger immigrant communities. Operating with minimal human services and limited recourse to the social and institutional networks of immigrant workers, labor coalitions in St. Louis and Indianapolis face recurrent barriers to identifying workplace problems, mobilizing low‐wage workers and sustaining citywide reform campaigns. This indicates geographical limits to the current organizing model and highlights the limitations of urban scholarship derived from large cities unrepresentative of urbanity as a whole.